PENGEMBANGAN MEDIA KARTU IDEKU UNTUK MENENTUKAN IDE POKOK PARAGRAF PADA SISWA KELAS IV MIM UNGGULAN KOTA GORONTALO - Siti Rahmatia Tuki; Wiwy T. Pulukadang; Fidyawati Monoarfa; Rusmin Husain; Rustam I. Husain (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the difficulties fourth-grade students at MIM Unggulan Gorontalo City face in determining the main idea of paragraphs, as well as the limited learning media available to them. This study aims to identify the initial conditions of learning media in fourth-grade classes at MIM Unggulan Gorontalo City, examine the development process of Ideku Card media, and assess the feasibility of Ideku Card media in helping students determine the main idea of paragraphs. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results showed that the Ideku Card learning media was categorized as